If it's not what You are looking for type in the equation solver your own equation and let us solve it.
h in (-oo:+oo)
((2*h)/2)*h = 1 // - 1
((2*h)/2)*h-1 = 0
1*h^2 = 1 // : 1
h^2 = 1
h^2 = 1 // ^ 1/2
abs(h) = 1
h = 1 or h = -1
h in { 1, -1 }
| J-37.4=105.29 | | f(x)=-3x^2+7x+5 | | 6s-28=-48+s | | 3(y+2)=a(5-2y) | | 11.2=f-1.8 | | R+2.1=4.7 | | -4x^2-5x+6=0 | | 180=x+(4x+30) | | 30/x+5.50=8 | | 13-3/4t=6 | | x^2+2x-128=0 | | 30/x-5.50=8 | | 42x^2-69x+20=7xQ^2-8 | | R+2.1=f-1.8 | | (x+3)+(x+11)=x(x+8)+57 | | X/3+x/4=8/3 | | 7x=168 | | x+12-2x= | | (a+b)(a+b)=0 | | 44.5-[4*(2+12)-22.7]= | | 3x+12-2x= | | 3x+4-2x= | | (9x^3+15x^2-24x-16)/(3x-4) | | J-87.4=115.06 | | 2(3r+2)=18 | | (2p-5)=(p+5) | | 21=36+x/30 | | x/4+6=2x-10 | | (5-3+8)x= | | (3y+4)=(5y-10) | | P+3/5=8/10 | | 29-2t=19 |